Cyanide Degradation from Mining Effluent Using Two Reagents: Sodium Metabisulphite and the Metabisulphite Mixture with Hydrogen Peroxide - Arangurí Llerena, Gonzalo; Reyes López, Iván (TECCIENCIA, 2018)
Cyanide ion (CN-) is widely used in different industrial operations, such as jewelry, steel manufacture, gold and silver extraction and electroplating. However, industrial emissions containing the CNion have to be treated to comply with environmental regulations. This research aimed to degrade free cyanide (CNL) present in the tailing of a metallurgical plant that processes gold-bearing ores and uses sodium cyanide (NaCN) as a leaching reagent. Sodium metabisulfite (Na2S2O5) and sodium metabisulfite with hydrogen peroxide (Na2S2O5 + H2O2) were used as oxidizing agents. To evaluate the effect of the factors, we used a factorial design with three independent variables: stirring time, reagent excess percentage, type of reagent and a dependent variable: CNL degradation (mg/L). According to the analysis of variance (ANOVA), the variables influenced significantly CNL degradation, being the most relevant the reagent excess percentage and according to the results, the maximum CNL degradation was 97.67% when 400% of Na2S2O5 was added with 4 hours of stirring.